Green RP-HPLC method for impurity profile of amlodipine in tablets - Gigopulu, Olga; Godzo, Hrisanta; Atanasovska, Biljana; Zafirova Gjorgievska, Marija; Poceva Panovska, Ana; Tonic-Ribarska, Jasmina; Acevska, Jelena; Brezovska, Katerina; Nakov, Natalija (Archives of Pharmacy, 2024)
Increased awareness of nature preservation has encouraged the introduction of the green analytical chemistry (GAC) practice concepts concerning several important aspects, including sustainable development, environmental impact, and minimum waste. The aim of this research was to contribute to the implementation of this approach for the pharmaceutical industry while retaining the crucial aspects and strict requirements of quality control of medicines. Therefore, an ethanol-based, green and robust high-performance liquid chromatography (HPLC) method for the determination of related substances of amlodipine (AML) in film-coated tablets was developed and optimized using the Design of Experiments (DoE). The chromatographic separation was performed on an RP-select B column (250 x 4.0 mm, 5 μm), using a mixture of 0.04 M sodium dihydrogen phosphate monohydrate (pH 4.0) and ethanol (60:40 % v/v) as a mobile phase. The optimized conditions provided the separation of two specified impurities (impurity D and impurity F). The selectivity of the method was confirmed using forced degradation studies. The Analytical Eco-scale approach and AGREE metrics confirmed that the method conforms to the GAC principles. The validated method was successfully applied for the determination of related substances in three samples from the market, demonstrating the applicability of the method in routine analysis.
Keywords: amlodipine; impurity profile; green method; HPLC; greenness evaluation